Infestation level and population dynamics of aphid on mustard - Mandal, E; Amin, MR; Rahman, H; Akanda, AM (Bangladesh Journal of Agricultural Research, 2018)
Mustard (Brassica juncea) variety BARI Shorisha-11 was cultivated during September 2016 to March 2017 in Gazipur, Bangladesh to find out the population dynamics of aphid and its infestation level on mustard. The aphid Lipaphis erysimi (Homoptera: Aphididae) was abundant in the field and caused infestation. The population of aphid in the mustard field showed fluctuation and reached to the peak at 22 December which was 289 per plant. Inflorescence had significantly higher level of infestation compared to individual siliqua and leaf. The daily mean temperature had significant negative, light intensity had insignificant negative and relative humidity had insignificant positive correlation with the abundance of aphid. The multiple linear regression analysis showed that the weather parameters namely temperature, light intensity and relative humidity individually as well as combindly contributed on the abundance of aphid, but the temperature had greater effect than other factors. Bangladesh J. Agril. Res. 43(4): 611-618, December 2018